Formation of Student Management Culture as A Pedagogical Problem - Hamdamova Mahzuna Tursunovna (Genius Publishing Group, 2023)
This article highlights the content and essence of pedagogical and psychological characteristics of the management culture of future educators, the concepts of “management culture”, “culture”.
Keywords: future educators; management culture; culture; specialist